Regular long-term red blood cell transfusions for managing chronic chest complications in sickle cell disease (Review) - Estcourt, L; Fortin, P; Hopewell, S; Trivella, M; Hambleton, I; Cho, G (Cochrane Collaboration, 2016)
Background Sickle cell disease is a genetic haemoglobin disorder, which can cause severe pain, significant end-organ damage, pulmonary complications, and premature death. Sickle cell disease is one of the most common severe monogenic disorders in the world, due to the inheritance of two abnormal haemoglobin (beta globin) genes. The two most common chronic chest complications due to sickle cell disease are pulmonary hypertension and chronic sickle lung disease. These complications can lead to morbidity (such as reduced exercise tolerance) and increased mortality. This is an update of a Cochrane review first published in 2011 and updated in 2014. Objectives We wanted to determine whether trials involving people with sickle cell disease that compare regular long-term blood transfusion regimens with standard care, hydroxycarbamide (hydroxyurea) any other drug treatment show differences in the following: mortality associated with chronic chest complications; severity of established chronic chest complications; development and progression of chronic chest complications; serious adverse events. Search Methods We searched the Cochrane Cystic Fibrosis and Genetic Disorders Group’s Haemoglobinopathies Trials Register. Date of the last search: 25 April 2016. We also searched for randomised controlled trials in the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library, Issue 1, 26 January 2016), MEDLINE (from 1946), Embase (from 1974), CINAHL (from 1937), the Transfusion Evidence Library (from 1950), and ongoing trial databases to 26 January 2016. Selection Criteria We included randomised controlled trials of people of any age with one of four common sickle cell disease genotypes, i.e. Hb SS, Sß0, SC, or Sß+ that compared regular red blood cell transfusion regimens (either simple or exchange transfusions) to hydroxycarbamide, any other drug treatment, or to standard care that were aimed at reducing the development or progression of chronic chest complications (chronic sickle lung and pulmonary hypertension). Data Collection and Analysis We used the standard methodological procedures expected by Cochrane. Main Results No studies matching the selection criteria were found. Authors' Conclusions There is a need for randomised controlled trials looking at the role of long-term transfusion therapy in pulmonary hypertension and chronic sickle lung disease. Due to the chronic nature of the conditions, such trials should aim to use a combination of objective and subjective measures to assess participants repeatedly before and after the intervention.